THE USE OF PREFABRICATED BASALT-PLASTIC REINFORCEMENT IN CONSTRUCTION - Ibodullayev Shermukhammad O’ktam O’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
There probably aren't many domed concrete structures where you live, because they're difficult to build. To build them usually requires the construction of a supporting wooden structure that holds the concrete in place while it is hardens. However, nowadays, a team at the Vienna University of Technology has devised a system that allows concrete shell structures to simply be "inflated" and cinched together with a steel cable.